The contribution of international health volunteers to the health workforce in sub-Saharan Africa - Bogaert Isa; Van der Roost Dirk; Marchal Bruno; Kegels Guy; Laleman Geert; Van Damme Wim (BMC, 2007)
Abstract Background In this paper, we aim to quantify the contribution of international health volunteers to the health workforce in sub-Saharan Africa and to explore the perceptions of health service managers regarding these volunteers. Methods Rapid survey among organizations sending international health volunteers and group discussions with experienced medical officers from sub-Saharan African countries. Results We contacted 13 volunteer organizations having more than 10 full-time equivalent international health volunteers in sub-Saharan Africa and estimated that they employed together 2072 full-time equivalent international health volunteers in 2005. The numbers sent by secular non-governmental organizations (NGOs) is growing, while the number sent by development NGOs, including faith-based organizations, is mostly decreasing. The cost is estimated at between US$36 000 and US$50 000 per expatriate volunteer per year. There are trends towards more employment of international health volunteers from low-income countries and of national medical staff. Country experts express more negative views about international health volunteers than positive ones. They see them as increasingly paradoxical in view of the existence of urban unemployed doctors and nurses in most countries. Creating conditions for employment and training of national staff is strongly favoured as an alternative. Only in exceptional circumstances is sending international health volunteers viewed as a defendable temporary measure. Conclusion We estimate that not more than 5000 full-time equivalent international health volunteers were working in sub-Saharan Africa in 2005, of which not more than 1500 were doctors. A distinction should be made between (1) secular medical humanitarian NGOs, (2)development NGOs, and (3) volunteer organizations, as Voluntary Service Overseas (VSO) and United Nations volunteers (UNV). They have different views, undergo different trends and are differently appreciated by government officials. International health volunteers contribute relatively small numbers to the health workforce in sub-Saharan Africa, and it seems unlikely that they will do more in the future. In areas where they play a role, their contribution to service delivery is sometimes very significant.